ANALISIS UNSUR HARA TANAH PODZOLIK MERAH KUNING SEBAGAI REKOMENDASI PEMUPUKAN TANAMAN KAKAO UMUR 0 – 1 TAHUN - Begum Fauziyah (El-QUDWAH, 2010)
Soil is the natural media for growing plants that contains organic materials such as macronutrient, micronutrient and tracer. According to the amount of the nutrient, soil is distinguished into three classifications; they are low nutrient, average nutrient and high nutrient. The amount of the elements influences the productivity of the planted plants. Therefore, soil with low and average nutrient needs a fertilization to increase its productivity. The suggested amount of the administered fertilizer, usually called recommended fertilization, is given after such analysis was done as, soil nutrient analysis; plant tissue analysis or fertilization result analysis. In this research, the recommended fertilization is made based on the soil nutrient of N, P, K, C, Ca, Fe, Zn, Mn, Mg and sulfate from the soil sample typed yellow red podzolic which is a kind of soil with average nutrient. The recommended fertilization is made for cacao at the age of 0-1, with the rooting radius 10 cm, the depth 10 cm and the volume weight 1.2 kg/L. The results show that the sample soil needs some additional nutrients of N, P, K, Ca, Mg and sulfate. The need of nutrient from each element is (in gram) 2.753; 0.122; 384.2; 2437.4; 574.5 and 0.05606.